Major Depression and Obsessive-compulsive Disorder Treated with Deep Brain Stimulation of Bilateral Nucleus Accumbens: The First Case of Turkey - Aydın, Sabri (Asian J Neurosurg, 2018)
Deep brain stimulation (DBS) is a new alternative treatment for treatment-resistant major depression (MD) and obsessive-compulsive disorder (OCD). Various DBS targets were defined for MD and OCD. Nucleus accumbens (NAcc) comes out among the other targets in patients with MD and comorbid OCD when physiopathology and limited side effects are taken into account. We report a 27-year-old male with MD and OCD who was treated by bilateral NAcc-DBS. The aim of this study is to discuss NAcc as a DBS target in patients with MD and OCD and to report the first case of a psychiatric disorder treated with DBS in Turkey.